2004
DOI: 10.1074/jbc.m401008200
|View full text |Cite
|
Sign up to set email alerts
|

Global Co-ordination of Protein Translocation by the SecA IRA1 Switch

Abstract: SecA, the dimeric ATPase subunit of protein translocase, contains a DEAD helicase catalytic core that binds to a regulatory C-terminal domain. We now demonstrate that IRA1, a conserved helix-loop-helix structure in the C-domain, controls C-domain conformation through direct interdomain contacts. C-domain conformational changes are transmitted to the DEAD motor and alter its conformation. These interactions establish DEAD motor/C-domain conformational cross-talk that requires a functional IRA1. IRA1-controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
106
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(110 citation statements)
references
References 40 publications
3
106
0
1
Order By: Relevance
“…They also identified another region that had synergistic effects, and termed it IRA2 and the first segment IRA1. 69,70 IRA2, in fact, is the second helicase domain, which was clear once the crystal structure was available.…”
Section: Seca Is Central To the Bacterial Sec Pathwaymentioning
confidence: 98%
See 1 more Smart Citation
“…They also identified another region that had synergistic effects, and termed it IRA2 and the first segment IRA1. 69,70 IRA2, in fact, is the second helicase domain, which was clear once the crystal structure was available.…”
Section: Seca Is Central To the Bacterial Sec Pathwaymentioning
confidence: 98%
“…Studies from a variety of groups over the past decade have revealed that SecA is a multidomain protein that can exist as a monomer or a dimer, and that its domain rearrangements can be triggered by binding to any of its several ligands. 67,[69][70][71][72][73][74][75][76][77][78][79][80][81] The key to the conformational rearrangements appears to be intramolecular interactions that stabilize a more tightly packed, ''closed'' form of the protein. Weakening these interactions relieves these intramolecular constraints, and the protein domains partially dissociate, creating a less tightly packed, ''open'' form of the protein.…”
Section: Seca Is Central To the Bacterial Sec Pathwaymentioning
confidence: 99%
“…These results as well as the results of Dapic and Oliver (37) that a N-terminal fragment of SecA is sufficient for the high affinity binding to SecYEG are consistent with our proposal made in this work that the ATPase itself can sense SecYEG as an activating ligand. The maximum ATPase up-regulation, which requires preprotein binding as well, must be accompanied by a substantial conformational change of the ATPase domain (32) to facilitate the arginine finger access to the ATP ␥-phosphate and possibly to induce the swinging movement of HSD.…”
Section: Discussionmentioning
confidence: 99%
“…Tyr-326 has been found to be critical in controlling . An N-terminally truncated SecA, representing the activated state, has been found to have high ATPase activity, binds the signal peptide with significantly higher affinity than WT SecA, and exists in a monomeric form (8,35). This suggests that the affinity of the signal peptide for SecA depends on its conformational state (36).…”
Section: Introductionmentioning
confidence: 99%